Use of the concept of ‘product’ to analyze the relationships between tourism and physical culture - Szczechowicz, Bartosz (Turyzm/Tourism, 2013)
The purpose of this article is to present opportunities for research which show the common ground between tourism and physical culture using approaches and methods worked out and applied in economics. Attention has been concentrated on the category of ‘product’, treated here as a theoretical concept by means of which it is possible to present a structure of tourism trip. This will include the part that refers to those values and human activities related to physical culture. An attempt to identify the social perception of the attributes that describe a tourism trip was made by an empirical study using conjoint analysis on students in higher education in Kraków. The results show that those who participate in tourism enriched by physical activity, prefer trips saturated with attributes such as the required level of courage, the testing of psychological and physical abilities, rivalry with others or nature, an element of adventure, a high level of physical activity, access to sports and leisure facilities, and contact with nature. But at the same time they prefer a low level of risk to health or life. It was noted, however, that related to the latter female and male preferences vary.